Bis(phosphine)boronium salts. Synthesis, structures and coordination chemistry. - Shuttleworth, T; Huertos, M; Pernik, I; Young, R; Weller, A (2013)
The synthesis of a range of bis(phosphine)boronium salts is reported [(R2HP)2BH2][X] (R = Ph, (t)Bu, Cy) in which the counter anion is also varied (X(-) = Br(-), [OTf](-), [BAr(F)4](-), Ar(F) = 3,5-(CF3)2C6H3). Characterization in the solid-state by X-ray diffraction suggests there are weak hydrogen bonds between the PH units of the boronium cation and the anion (X(-) = Br(-), [OTf](-)), while solution NMR spectroscopy also reveals hydrogen bonding occurs in the order [BAr(F)4](-) < [OTf](-) < Br(-). [(Ph2HP)2BH2][BAr(F)4] reacts with RhH(PPh3)3, by elimination of H2, forming [Rh(κ(1),η-PPh2BH2·PPh2H)(PPh3)2][BAr(F)4] which shows a β-B-agostic interaction from the resulting base stabilised phosphino-borane ligand. Alternatively such ligands can be assembled directly on the metal centre by reaction of in situ generated {Rh(PPh3)3}(+) and Ph2HP·BH3 to afford [Rh(κ(1),η-PPh2BH2·PPh3)(PPh3)2][BAr(F)4], which was characterised by X-ray crystallography. Addition of H3B·PPh2H to the well-defined 16-electron "T-shaped" complex [Rh(P(i)Bu3)2(PPh3)][BAr(F)4] (characterised by X-ray crystallography) formed of a mixture of base-stabilised phosphino borane ligated complexes [Rh(κ(1),η-PR2BH2·PR3)(PR3)2][BAr(F)4] (R = (i)Bu or Ph). These last observations may lend clues to the formation of bis(phosphine)boronium salts in the catalytic dehydrocoupling reaction of phosphine boranes as mediated by Rh(I) compounds.